Insulin Secretion and Risk for Future Diabetes in Subjects with a Nonpositive Insulinogenic Index - Daisuke Aono; Rie Oka; Mitsuhiro Kometani; Yoshimichi Takeda; Shigehiro Karashima; Kenichi Yoshimura; Yoshiyu Takeda; Takashi Yoneda (Journal of Diabetes Research)
Aim. To characterize subjects with a nonpositive insulinogenic index and longitudinally observe changes in their glucose tolerance. Subjects and Methods. A historical cohort study was conducted using data from the medical checkups of public school workers. Indices of insulin secretion and insulin sensitivity derived from oral glucose tolerance test (OGTT) and the incidences of diabetes and impaired glucose tolerance (IGT) were compared among subgroups of subjects with different insulinogenic index (change in insulin/change in glucose over the first 30 min on the OGTT). Results. Of the 1464 nondiabetic subjects at baseline, 72 (4.9%) subjects had a nonpositive insulinogenic index: 42 of those subjects had a nonpositive glucose response (ΔGlu0–30 ≤ 0) and 30 had a nonpositive insulin response (ΔIns0–30 ≤ 0). Compared with subjects who had normal glucose tolerance (NGT) with insulinogenic index ≥ 0.4, subjects with a nonpositive glucose response had a higher first-phase Stumvoll and lower incidences of diabetes and IGT based on a log-rank test (p<0.05), whereas subjects with a nonpositive insulin response had lower indices of insulin secretion and a higher incidence of diabetes (p<0.05). Conclusions. These results demonstrate that in the first 30 min on the OGTT, subjects with a nonpositive insulinogenic index due to a nonpositive glucose response (ΔGlu0–30 ≤ 0) had a lower risk for future diabetes and that subjects with nonpositive insulin response (ΔIns0–30 ≤ 0) had a higher risk for future one.